2018
DOI: 10.1159/000494031
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Carboplatin/Paclitaxel-Based Radiochemotherapy in Locally Advanced Squamous Cell Carcinoma of Head and Neck

Abstract: Background: Cisplatin-based chemotherapy (CTX) is commonly used concurrently with radiotherapy for head and neck cancer. The value of CTX regimens other than cisplatin for locally advanced squamous cell carcinoma of head and neck (LASCCHN) has not been well established. Here we compare the outcome of patients treated with different platinum-based chemotherapy regimens. Methods: Medical records from 104 patients with LASCCHN treated with radiochemotherapy (RCTX) between February 2013 and August 2016 were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Vlacich et al 78 reported that the 30-year locoregional control rate with intensity-modulated RT and concurrent carboplatin 1 paclitaxel was 83.2%, with disease-free survival and overall survival rates of 78.8% and 76.5%, respectively. Maring et al 79 reported a recurrence rate of 30% for patients treated with RT plus carboplatin 1 paclitaxel, compared with 38% of those treated with RT 1 cisplatin (P5.6). Event-free survival and overall survival were reported to be 30 and 28 months, respectively, for the RT plus carboplatin 1 paclitaxel group, versus 37 and 35 months, respectively, for the RT 1 cisplatin group.…”
Section: Systemic Therapy For Squamous Cell Skin Cancermentioning
confidence: 99%
“…Vlacich et al 78 reported that the 30-year locoregional control rate with intensity-modulated RT and concurrent carboplatin 1 paclitaxel was 83.2%, with disease-free survival and overall survival rates of 78.8% and 76.5%, respectively. Maring et al 79 reported a recurrence rate of 30% for patients treated with RT plus carboplatin 1 paclitaxel, compared with 38% of those treated with RT 1 cisplatin (P5.6). Event-free survival and overall survival were reported to be 30 and 28 months, respectively, for the RT plus carboplatin 1 paclitaxel group, versus 37 and 35 months, respectively, for the RT 1 cisplatin group.…”
Section: Systemic Therapy For Squamous Cell Skin Cancermentioning
confidence: 99%
“…Carboplatin is a chemotherapeutic agent commonly used in the treatment of head and neck cancers. 14,43 The main target of carboplatin is DNA, where it binds and cross-links the bases in the strands. 44 These cross-links inhibit DNA replication and repair, leading to transcription errors and inhibition of cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…Carboplatin is a chemotherapeutic agent commonly used in the treatment of head and neck cancers 14,43 . The main target of carboplatin is DNA, where it binds and cross‐links the bases in the strands 44 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations